(untitled) (Research Journal of Mathematics & Technology, 2022)
Several researches show the potential of using new information and communication technologies (ICT) in the teaching and learning of mathematics. One of the branches in the teaching of mathematics that, over time, has deserved a special mention, is geometry, namely with the use of dynamic geometry systems (DGS). A learning environment for teaching and learning geometry, associated with tasks of an exploratory and investigative nature, tends to favor the discovery of properties and geometric relationships, which benefits the acquisition of knowledge and the production of evidence. In this article the learning environment Web Geometry Laboratory (WGL) was used in a case study for the exploration of visual proofs. The study was done with pre-service teachers. Conclusions are drawn and future work is foreseen.